Wesley : a guide for the perplexed - Vickers, Jason E. (London ; New York : T & T Clark, 2009)
John Wesley was one of the most enigmatic religious figures of the 18th century. This guide identifies some of the key factors contributing to the more perplexing aspects of his life and aids students understanding and knowledge.
John Wesley was one of the most enigmatic religious figures of the 18th century. This guide identifies some of the key factors contributing to the more perplexing aspects of his life and aids students understanding and knowledge.
Spreading the gospel: Methodism and the Evangelical Revival -- Keeping to the church: the stabilization of English society -- Honouring the king: the politics of divine right -- Loving God: a theology of joyful obedience.
Includes bibliographical references (p. 124-128) and index.
Keywords: Wesley, John, -- 1703-1791.